A simulators specifications for studying students engagement in a classroom - Subramainan L.; Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M. (Springer Verlag, 2023)
Artificial intelligence; Distributed computer systems; Education; Simulators; Specifications; Teaching; Agent based; Agent based social simulation; Emotional engagements; Emotional factors; Emotional state; Environmental factors; Students